2003
DOI: 10.1049/el:20030162
|View full text |Cite
|
Sign up to set email alerts
|

Radiation from ingested wireless devices in biomedical telemetry bands

Abstract: Glasgow ePrints Service http://eprints.gla.ac.uk 60" of arc with a radius of 51 and a height 1OA with A= 1 m. A vertical dipole is placed at a distance of 101 from the centre of the cylinder. Fig. 1 shows the interpolated values for the amplitude and the phase of the current on the cylinder. The difference between these values and the exact ones are shown in Fig. 2. As shown in Fig. 2 the interpolation error is negligible. The maximum relative errors in this case are 2.0 x IOp4 for the amplitude and 4.0 x IO-'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Results were attributed to the authors' choice of keeping the antennas' physical dimensions identical, and modifying their effective size. Studies for ingestible MDs have demonstrated adequate communication to take place between 600 and 1000 MHz [Chirwa et al, ], with maximum radiation occurring between 450 and 900 MHz [Chirwa et al, ], and a peak in the transmitted power being identified at approximately 650 MHz [Chirwa et al, ]. Furthermore, selection of operation frequency is directly related to bit rate: higher operation frequencies allow for an increase in bandwidth and enable higher bit rates, which are favorable for high data rate applications, such as the real‐time video transmission of ingestible MDs.…”
Section: Operation Frequency Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were attributed to the authors' choice of keeping the antennas' physical dimensions identical, and modifying their effective size. Studies for ingestible MDs have demonstrated adequate communication to take place between 600 and 1000 MHz [Chirwa et al, ], with maximum radiation occurring between 450 and 900 MHz [Chirwa et al, ], and a peak in the transmitted power being identified at approximately 650 MHz [Chirwa et al, ]. Furthermore, selection of operation frequency is directly related to bit rate: higher operation frequencies allow for an increase in bandwidth and enable higher bit rates, which are favorable for high data rate applications, such as the real‐time video transmission of ingestible MDs.…”
Section: Operation Frequency Selectionmentioning
confidence: 99%
“…For the majority of positions, vertically polarized radiation has been found to attenuate more than horizontal radiation [Chirwa et al, ], and intensity of the electric field in the anterior of the human body has been shown to be, generally, higher than that in the posterior [Xu et al, ]. In Chirwa et al [], the radiated field was found to be predominantly strongest in the same horizontal transverse plane as the source, and in the direction that was on the line from the source to the nearest body surface. Therefore, the optimum location for a receiver antenna would be an anterior location slightly to the left of the abdomen (as the small intestine does not extend so much to the right due to the presence of the colon).…”
Section: Antenna Design and Performancementioning
confidence: 99%
“…So, with www.intechopen.com the change from free space to body materials, dielectric constant changes from 1 to 56 and conductivity changes from 0 to 0.8. What's more, to detect the transmitted signal independent of transmitter a position, the antenna is required the omni-directional radiation pattern (Kim & Rahmat-Samii, 2004;Chirwa et al, 2003). To investigate the characteristics of antennas for capsule endoscope, the human body is considered as an averaged homogeneous medium as described by the Federal Communications Commission (FCC) and measured using a human phantom (Kwak et al, 2005;Haga et al, 2009).…”
Section: Special Consideration Of Body Characteristics For Antenna Dementioning
confidence: 99%
“…Thus, several researchers have been studying high efficiency antennas for capsule endoscopes [2,3,4]. Generally, the maximum size of an ingestible capsule endoscope is a length of 20 mm and a diameter of 10 mm [1].…”
Section: Introductionmentioning
confidence: 99%